2003
DOI: 10.1210/er.2001-0025
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Coronary Artery Disease

Abstract: A significant and independent association between endogenous testosterone (T) levels and coronary events in men and women has not been confirmed in large prospective studies, although cross-sectional data have suggested coronary heart disease can be associated with low T in men. Hypoandrogenemia in men and hyperandrogenemia in women are associated with visceral obesity; insulin resistance; low high-density lipoprotein (HDL) cholesterol (HDL-C); and elevated triglycerides, low-density lipoprotein cholesterol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(80 citation statements)
references
References 379 publications
(179 reference statements)
0
77
1
2
Order By: Relevance
“…There was no change in the total to HDL-cholesterol ratio, a standard measure of coronary heart disease risk (64), although a small increase of uncertain clinical relevance in LDL-cholesterol was observed. In other studies, testosterone therapy has been reported to either decrease (65,66) or not change LDL-cholesterol (53,56,67,68,69). There were no changes to lipid-lowering therapy during the course of the study, suggesting that the changes in LDL-cholesterol were not as a result of alterations in concomitant medications.…”
Section: Discussionmentioning
confidence: 58%
“…There was no change in the total to HDL-cholesterol ratio, a standard measure of coronary heart disease risk (64), although a small increase of uncertain clinical relevance in LDL-cholesterol was observed. In other studies, testosterone therapy has been reported to either decrease (65,66) or not change LDL-cholesterol (53,56,67,68,69). There were no changes to lipid-lowering therapy during the course of the study, suggesting that the changes in LDL-cholesterol were not as a result of alterations in concomitant medications.…”
Section: Discussionmentioning
confidence: 58%
“…Our finding of a strong inverse association of total and free testosterone concentrations with non-esterified free fatty acids is consistent with this hypothesis. Exogenous testosterone may also have a favourable effect on the lipid profile, although HDL levels have sometimes decreased (34). Whether testosterone mediates its effect on blood pressure indirectly through the association of testosterone with the metabolic syndrome or directly through effects on the vascular endothelium is not known (34).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on SHBG gene polymorphisms have shown an association of the SHBG gene promoter polymorphism with the severity of CAD, as well as early markers of atherosclerosis in postmenopausal women (34,35). However, discussing studies on the clinical relevance of SHBG in cardio-and cerebro-vascular disease is not part of this review and the reader is referred to recent reviews (36,37).…”
Section: Severity and Mortality Of Cardio-and Cerebro-vascular Diseasementioning
confidence: 99%